The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1088/0029-5515/38/2/308
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of a compact toroid tangentially injected into a tokamak

Abstract: A compact toroid (CT) penetrating into a tokamak discharge is modelled as a conducting solid sphere with an intrinsic magnetic moment. Equations of CT motion in tokamak discharges are derived and used to calculate the trajectory of a CT with parameters pertinent for penetrating the ITER tokamak. The advantage of tangential CT injection and the optimal direction of the initial magnetic moment are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Some theoretical studies show that tangential CT injection has longer interaction time with the tokamak plasma and might cause smaller disturbance on the tokamak discharge. 10,11 In addition, tangential CT injection may transfer CT momentum to tokamak plasma to induce and sustain toroidal rotation, which has beneficial effects on stabilizing the locked mode and resistive wall mode. 12 At the University of Saskatchewan, it has been observed that tangential CT injection into the Saskatchewan Torus-Modified ͑STOR-M͒ tokamak induces H-mode discharges.…”
Section: Introductionmentioning
confidence: 99%
“…Some theoretical studies show that tangential CT injection has longer interaction time with the tokamak plasma and might cause smaller disturbance on the tokamak discharge. 10,11 In addition, tangential CT injection may transfer CT momentum to tokamak plasma to induce and sustain toroidal rotation, which has beneficial effects on stabilizing the locked mode and resistive wall mode. 12 At the University of Saskatchewan, it has been observed that tangential CT injection into the Saskatchewan Torus-Modified ͑STOR-M͒ tokamak induces H-mode discharges.…”
Section: Introductionmentioning
confidence: 99%
“…Benefits of CT injection are that it is able to penetrate into the core region of the tokamak plasma as it is an excellent conductor with a high velocity and is able to overcome the tokamak's toroidal field gradient. Also, via tangential injection, CT injection provides long interaction time with tokamak plasma, and transfers momentum to the tokamak plasma, causing smaller disturbances in the discharge and inducing and sustaining toroidal rotation [26,27].…”
Section: Nuclear Fusion and The Tokamak Reactormentioning
confidence: 99%
“…The wave's frequency, ω, must be larger than the plasma frequency, 27) where ω has a dispersion relation…”
Section: Interferometrymentioning
confidence: 99%
“…The CS model was developed further by Newcomb [8], who developed a more accurate model for the MHD wave drag. Xiao et al [9] refined the work of Bozhokin and used the corrected (Newcomb) drag term, and also were the first to simulate vertical (as opposed to radial) injection [10]. All these models had three degrees of freedom, considering the motion of the CT in a twodimensional plane and the rotation of its dipole about a single fixed axis.…”
Section: The Conducting Sphere (Cs) Modelmentioning
confidence: 99%
“…Several papers [5,7,9,12,13] have used ITER or ITER-like reactors as test cases for the CT trajectory models. In addition, there have been at least two [24,25] serious proposals to use horizontal CT injection as a central fuelling method for ITER.…”
Section: Application To Itermentioning
confidence: 99%